“Poesia” senza poesia: Franz Kafka, Maria Callas (Materiali di Estetica. Terza serie, 2020)
The poetic world includes both poetry to be intended as a specific literary genre and a wider poeticity diffused in the artistic sphere and elsewhere. In this contribution I will consider from my own point of view two highly significant cases of the artistic world: Franz Kafka and Maria Callas. The great attraction that Kafka has exerted on me since the last years of high school has been triggered by passages mentioned by Remo Cantoni in his Introductions to The Castle, to the Diaries, to the Letters to Milena ecc. In the same years I used to attend Teatro alla Scala where Maria Callas performed. These events are apparently so distant from each other, but they are very close in my experience because of the intense poeticity that innervates both.
Keywords: Poetry; Poeticity; Writing; Bel Canto; Musical Theatre